Biomass accumulation and carbon sequestration potential in varying tree species, ages and densities in Gunung Bromo Education Forest, Central Java, Indonesia - AHMAD ARIF DARMAWAN; DWI PRIYO ARIYANTO; TYAS MUTIARA BASUKI; JAUHARI SYAMSIYAH; WIDYATMANI SIH DEWI (Society for Indonesian Biodiversity, 2022)
Abstract. Darmawan AA, Ariyanto DP, Basuki TM, Syamsiyah J, Dewi WS. 2022. Biomass accumulation and carbon sequestration potential in varying tree species, ages and densities in Gunung Bromo Education Forest, Central Java, Indonesia. Biodiversitas 23: 5093-5100. Forest biomass plays an important role in carbon storage to mitigate climate change. While many studies have investigated the carbon stock of various forests, adding knowledge in the context of education forest might enrich the importance of this forest as a carbon pool besides its role for education purposes. Gunung Bromo Education Forest in Karanganyar Regency, Central Java, Indonesia consists of several tree cover types with each type having a different ability to absorb carbon dioxide in the atmosphere. This research aimed to determine the accumulation of biomass in Gunung Bromo Education Forest and to investigate the potential for carbon sequestration across different tree species, age classes and densities. Three species of tree (i.e. pine, Indonesian rosewood and mahogany) with varying ages were measured and calculated the biomass (i.e. tree, litter and understorey) and total carbon sequestration potentials (i.e. tree, litter and understorey, and soil organic carbon). This study used purposive sampling method across 9 combinations of tree cover type and age classes, each with 3 replication, resulting in a total of 27 sampling points. The results showed pine stands planted in 1973 had the highest tree biomass of 461.08 t ha-1 and while the pine agroforest planted in 2016 and Indonesian rosewood agroforest planted in 2018 had the lowest tree biomass with 1.02 t ha-1 and 0.39 t ha-1, respectively. Similarly, the pine stands planted in 1973 had the highest total carbon sequestration of 372.68 t ha-1 and the lowest in the pine agroforest planted in 2016 and Indonesian rosewood agroforest planted in 2018 with 187.11 t ha-1 and 193.58 t ha-1 respectively. The results of this study strengthen the common agreement in previous carbon studies that tree age strongly affects biomass accumulation and carbon sequestration, in which the older the plant, the higher the carbon sequestration potential than that of younger plants.